Data-Driven Analytical Tools for Characterization of Productivity and Service Quality Issues in IT Service Factories. (August 2013) - Cavalcante, Victor F.; Pinhanez, Claudio S.; Paula, Rogério A. de; Andrade, Carolina S.; de Souza, Cleidson R. B.; Appel, Ana P.
In this article, we propose an analytical tool, named the Workload Profile Diagnosis ( WPD ) method, to evaluate the performance and quality of incident management (IM) systems in information technology (IT) service factories. Based on the normalization of ticket assignment delay and resolution time by their respective service-level agreement, the method computes and plots the spreading of ticket data on a log-log chart. By comparing the actual and desired distribution values in specific areas, the WPD method diagnoses specific problems and issues in the performance of IM systems such as resource and skill allocation and abnormal behavior, and identifies opportunities for automated resolution or assignment of tickets, increases or decreases in the resources and skills needed, and ultimately aims to strike a better balance between productivity and service quality. In addition to an in-depth description of the WPD method, this article presents its application in the diagnostics of four service pools of a large IT service factory. An empirical study conducted in the IT service factory shows that most of the problems identified by the WPD method were indeed present in the service pools, therefore providing evidence of the validity of the WPD method. We conclude discussing how managers can use the method to detect and evaluate transformational opportunities to increase productivity and service quality in a systematic manner.